2017
DOI: 10.3390/nu9040342
|View full text |Cite
|
Sign up to set email alerts
|

Gelidium elegans Regulates the AMPK-PRDM16-UCP-1 Pathway and Has a Synergistic Effect with Orlistat on Obesity-Associated Features in Mice Fed a High-Fat Diet

Abstract: The incidence of obesity is rising at an alarming rate throughout the world and is becoming a major public health concern with incalculable social and economic costs. Gelidium elegans (GENS), also previously known as Gelidium amansii, has been shown to exhibit anti-obesity effects. Nevertheless, the mechanism by which GENS is able to do this remains unclear. In the present study, our results showed that GENS prevents high-fat diet (HFD)-induced weight gain through modulation of the adenosine monophosphate-acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 54 publications
2
44
0
Order By: Relevance
“…In this regard, Gao et al, () have successfully demonstrated the reduction of body weight gain in mice was mediated by an increase in energy expenditure and fatty acid oxidation through the actions of PGC‐1α and UCP‐1 in their study on butyrate supplementation. In addition, other studies have demonstrated the involvement of the adenosine monophosphate‐activated protein kinase (AMPK)‐PR domain‐containing16 (PRDM16)‐uncoupling protein‐1 (UCP‐1) pathway in increased calorie expenditure in mice models (Choi, Kim, Koh, & Lee, ; Kudo et al, ). AMPK regulates energy metabolism by stimulating the interaction between PGC1α and PRDM16 resulting in increased mitochondrial biogenesis, thermogenesis, and energy expenditure (Zhang et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, Gao et al, () have successfully demonstrated the reduction of body weight gain in mice was mediated by an increase in energy expenditure and fatty acid oxidation through the actions of PGC‐1α and UCP‐1 in their study on butyrate supplementation. In addition, other studies have demonstrated the involvement of the adenosine monophosphate‐activated protein kinase (AMPK)‐PR domain‐containing16 (PRDM16)‐uncoupling protein‐1 (UCP‐1) pathway in increased calorie expenditure in mice models (Choi, Kim, Koh, & Lee, ; Kudo et al, ). AMPK regulates energy metabolism by stimulating the interaction between PGC1α and PRDM16 resulting in increased mitochondrial biogenesis, thermogenesis, and energy expenditure (Zhang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…PGC-1α is known to stimulate adaptive thermogenesis in brown fat by upregulating uncoupling protein 1 (UCP-1), which in turn increases oxidative type 1 fiber differentiation and enhances fatty acid metabolism in the muscle. In this regard, Gao et al, (2009) (UCP-1) pathway in increased calorie expenditure in mice models (Choi, Kim, Koh, & Lee, 2017;Kudo et al, 2015). AMPK regulates energy metabolism by stimulating the interaction between PGC1α and PRDM16 resulting in increased mitochondrial biogenesis, thermogenesis, and energy expenditure .…”
Section: Discussionmentioning
confidence: 99%
“…One example of note is Gelidium elegans extract (GEE), previously known as Gelidium amansii , an edible seaweed native to the Asia Pacific region [ 31 ]. We have described the bioactivity of GEE, including its anti-oxidant, anti-hyperglycemic, and anti-obesity effects [ 32 , 33 , 34 ]. Our previous study showed that GEE has the potential to regulate energy metabolism in high fat diet-induced obese mice [ 32 ], and in particular it may regulate glucose homeostasis [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…AMP-activated protein kinase (AMPK) has emerged as a key regulator in hepatic energy metabolism and lipid homeostasis. Activation of AMPK suppresses fatty acid and cholesterol biosynthesis, by inhibiting the activity of acetyl CoA carboxylase (ACC) and 3-hydroxy-3-methyl glutaryl CoA reductase (HMGR; Li et al, 2014 ; Choi et al, 2017 ). In addition, AMPK can inactivate sterol regulatory element-binding proteins (SREBPs), the major transcriptional regulators of lipogenesis, and thereby inhibit the downstream lipogenic genes (Jang et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%